Synthesis of Thioethers from Sulfonyl Chlorides, Sodium Sulfinates, and Sulfonyl Hydrazides - Wu, Ronghai; Huang, Keke; Qiu, Guanyinsheng; Liu, Jin-Biao (Synthesis, 2019)
Sulfur-containing moieties, especially thioethers (sulfides), play pivotal roles in the functionalities of many natural products, pharmaceutical compounds, and organic materials. In this review, we summarize the recent synthetic protocols of thioethers using thiolating reagents, including sulfonyl chlorides, sodium sulfinates, and sulfonyl hydrazides, as the ideal starting materials. Representative mechanisms for different types of reaction are also discussed.1 Introduction2 Synthesis of Thioethers from Sulfonyl Chlorides3 Synthesis of Thioethers from Sodium Sulfinates4 Synthesis of Thioethers from Sulfonyl Hydrazides5 Conclusion
Keywords: thiolation; thioethers; sulfonyl chlorides; sulfonates; sulfonyl hydrazides; carbon–sulfur bond